Plato's Breath - Freisinger, Randall R. (Utah State University, University Libraries, 1997)
May Swenson Poetry Award Volume 1 with foreward by Herbert Leibowitz. Freisinger's new poetry collection is inhabited alike by bright, tangible images and thoughtful, intricate meditations. Pumpkins, poultry houses, sperm tests, a vacuum cleaner salesman, a father's damaged brain, an anatomist's tools, a baby falling from a fourth-story window-all of these come to the page distinct and palpable. At the same time, the work finds a central inspiration in theoretical work like Jeremy Rifkin's social criticism. Poetry of both the mind and the heart, Plato's Breath embraces the power of imagination to transform the ordinary into an extraordinary affirmation of life.